Adobe Photoshop and Lightroom Classic for photographers - Concepcion, Rafael (Classroom in a book., 2023)
Lightroom and Photoshop are integral parts of a photographer's workflow for making great images. Start by importing and organizing your images into collections that make sense for you. Develop your pictures to make the most out of every pixel. Learn how Photoshop and Lightroom's new AI based tools can take your vision further faster. Learn the strengths of each program at each part of your workflow to help you realize your creative vision in no time at all. Adobe Photoshop and Lightroom Classic for Photographers Classroom in a Book contains 11 lessons that cover the basics and beyond, from sorting your photos and adjusting tone and color to leveraging AI-based masking and neural filters. You can follow the book from start to finish or choose only those lessons that interest you.